2016
DOI: 10.1590/2317-1782/20162015165
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre percepção auditiva e produção vocal em implantados cocleares: uma revisão sistemática

Abstract: None of the selected studies were rated at level 1 of scientific evidence or grade A of recommendation, which is related to the methodological approach that can go with this subject matter. There is great lack of publications relating auditory perception and speech production in cochlear implant users. This gap is even greater when it comes to the adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
3
1
3
Order By: Relevance
“…However, even with such a difference, the absolute values obtained in the auditory-perceptual analysis of the voice were similar, demonstrating that this information does not influence the voice sample of both groups. Although these were the results obtained in the present research, it is known that adults with prelingual HL, who were implanted late, when already an adult, can have important changes in their voice quality and speech production (15) . Thus, it is suggested that further studies be conducted to confirm this datum.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…However, even with such a difference, the absolute values obtained in the auditory-perceptual analysis of the voice were similar, demonstrating that this information does not influence the voice sample of both groups. Although these were the results obtained in the present research, it is known that adults with prelingual HL, who were implanted late, when already an adult, can have important changes in their voice quality and speech production (15) . Thus, it is suggested that further studies be conducted to confirm this datum.…”
Section: Discussioncontrasting
confidence: 79%
“…Furthermore, the higher degree of nasality and strain was notorious in the group with prelingual HL, a factor that can be associated with the incorrect velopharyngeal coordination during vocal production. It is further believed that the degree of nasality may have interfered with the overall impression on the voice quality, as nasality is an aspect commonly cited as a distinctive marker of the voice of people with HL (1,2,15,16) and that the subjects with a higher degree of nasality were those who, in this study, had a higher general degree of deviation in voice quality. This finding is possibly related to the difference in time of auditory deprivation and absence of feedback in both groups, as various studies present this factor as a great influence on the voice quality of the person with HL (4,18,24) .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Após o percurso da onda sonora durante as etapas do sistema auditivo periférico o estímulo recebido, ativa o sistema de processamento auditivo central, responsável pelas funções de discriminar, localizar e reconhecer o som, compreender e memorizar, (FILHO, 2013). De acordo com Capelli et al (2016), as tarefas desenvolvidas pelo Processamento Auditivo Central (PAC) são primordiais para a interpretação dos sons, e, por consequência, para a aquisição da língua oral.…”
Section: Referencial Teóricounclassified
“…Voice quality stands among the impact factors that can be mitigated (16) . Currently, some hearing-impaired children are undergoing a therapeutic process, benefiting from hearingrelated diagnostic and technological advances, while other children start intervention at a later age (17) .…”
Section: Introductionmentioning
confidence: 99%